(untitled) (Fiep Bulletin - online, 2015)
This article indicates the trajectory of the discipline, Body and Dialogues: Fundaments of Physical Education, which took place in the Pedagogic Training Course for Teachers in Service for junior schools at the Faculdade de Educação (Faculty of Education) UFPEL administered in Jaguarão-RS. The intention is to situate the paths based on the experiences carried out with films, interviews and other “readings” developed during the process. This work is characterized as a qualitative research mainly through the adopted procedures. André (1995:24) proposes the use of the term qualitative, in the following way: Differentiate collection techniques, or design collected data... Contribute to the training of sensitive educators; as, once the process of experience such as the expression of movement itself and emotion is detected, , we hope that we are also capable of working with movements, emotions, games, and toys thus creating renewable spaces of expressing vitality, affection, and creativity of sexuality and transcendence. The knowledge was collected through dialogues, listening and silence, presented through Friere’s book Pedagogy of the Anatomy, (1996). We learn through the expressions of the faces, looks and body language of the educators seeking to find sensitive signs in labyrinths and indications of new paths. Or rather, as indicated by Rolando Toro (2002) through his literature, build a poem of the moved human encounter. “Celebrate the presence of another; praise him in the essential charm of the encounter and perhaps the only healthy possibility”.